Analysis of Men’s Rights as Equality Movement in 21st Century - Suroyo, Suroyo; Putra, Bima Maulana (The Indonesian Journal of International Clinical Legal Education, 2023)
Men's problems and interests have been neglected and marginalized primarily because of feminism's political and cultural domination. The novelty of this study is that it provides a current perspective on men's rights in the twenty-first century. The qualitative design of the research relied on semi-structured interviews. Thematic analysis was performed on the data, which included 548 participants from Australia, Indonesia, and the United Kingdom that were classified in Affiliation, ethnicity, status, and gender. The data was collected from Quora as the major source and other platforms (Reddit, Facebook, Instagram, and Twitter) as supplementary sources. The purpose of this study is not to define anti-feminism. Instead, it describes men's rights, which may be used in any scenario where gender equality is a concern. As a result, supporters of men's rights are concerned about a wide range of issues, some of which have spawned their own organizations or movement, such as the fathers' rights movement, which is particularly concerned with divorce and child custody issues. Gender roles are at the heart of many issues concerning men's rights. In conclusion, men's rights should be treated equally with women's rights to achieve gender equality, and the terms "ladies first" and "Hercules syndrome" should be abolished.